Short-term toxicity studies of thallium (I) sulfate administered in drinking water to Sprague Dawley rats and B6C3F1/N mice - Kelly A. Shipkowski; Troy D. Hubbard; Kristen Ryan; Suramya Waidyanatha; Helen Cunny; Keith R. Shockley; Joshua L. Allen; Heather Toy; Keith Levine; James Harrington; Laura Betz; Barney Sparrow; et al. (Toxicology Reports, 2023)
Thallium is a heavy metal that is known to induce a broad spectrum of adverse health effects in humans including alopecia, neurotoxicity, and mortality following high dose acute poisoning events. Widespread human exposure to thallium may occur via consumption of contaminated drinking water; limited toxicity data are available to evaluate the corresponding public health risk. To address this data gap, the Division of Translational Toxicology conducted short-term toxicity studies of a monovalent thallium salt, thallium (I) sulfate. Thallium (I) sulfate was administered via dosed drinking water to time-mated Sprague Dawley (Hsd:Sprague Dawley® SD®) rats (F0 dams) and their offspring (F1) from gestation day (GD) 6 until up to postnatal day (PND) 28 at concentrations of 0, 3.13, 6.25, 12.5, 25, or 50 mg/L, and adult male and female B6C3F1/N mice for up to 2 weeks at concentrations of 0, 6.25, 12.5, 25, 50, or 100 mg/L. Rat dams in the 50 mg/L exposure group were removed during gestation, and dams and offspring in the 25 mg/L exposure group were removed on or before PND 0 due to overt toxicity. Exposure to thallium (I) sulfate at concentrations ≤ 12.5 mg/L did not impact F0 dam body weights, maintenance of pregnancy, littering parameters, or F1 survival (PND 4–28). However, in F1 pups, exposure to 12.5 mg/L thallium (I) sulfate resulted in decreased body weight gains relative to control rats and onset of whole-body alopecia. Measurement of thallium concentrations in dam plasma, amniotic fluid, fetuses (GD 18), and pup plasma (PND 4) indicated marked maternal transfer of thallium to offspring during gestation and lactation. Mice exposed to 100 mg/L thallium (I) sulfate were removed early due to overt toxicity, and mice exposed to ≥ 25 mg/L exhibited exposure concentration-related decreases in body weight. Lowest-observed-effect levels of 12.5 mg/L (rats) and 25 mg/L (mice) were determined based on the increased incidence of clinical signs of alopecia in F1 rat pups and significantly decreased body weights for both rats and mice.